Studi Kuat Tekan Paving Block dari Campuran Tanah, Semen, dan Abu Sekam Padi Menggunakan alat Pemadat Modifikasi - Sherliana, Sherliana; Iswan, Iswan; Setyanto, Setyanto (Universitas Lampung, 2016)
One of means transportation wich already familiar is paving block. Paving blocks made of amixture of portland cement or adhesive material like hydrolysis, water, and aggregates with orwithout other ingredients. However, the use of the material is made into high production rates.Therefore, in this study the process of manufacture of paving blocks will be tested using alternativematerials such as soil mixtures with rice husk ash additive materials derived from residualcombustion rice straw waste combined with portland cement.Soil samples were tested in this study are derived from clay Kota Baru, South Lampung are..Variations in content the mixture used was 0%, 7%, 9%, 11% and 13%, to 14 days curing timeand with burning treatment and without burning paving block samples. Based on the results ofphysical testing original soil, USCS soil samples classified as fine-grained soil and included in theCL group.The results showed that the manufacture of paving blocks using the soil material with additivematerials such as rice husk ash and cement did not fulfill SNI paving block. However, in generalthe addition of the additive materials can increase the physical and mechanical properties of thesoil. It is proved by the increasing value of the optimum moisture content and ductility of pavingblocks. For the compressive strength of paving blocks without and with burning process is bestshown in the addition of a mixture of 9% content.Keywords: Paving blocks, clay soil, compressive strength